(untitled) (Research, Society and Development, 2022)
Objective: This study aimed to understand the main difficulties and challenges faced by the Nursing team in coping with COVID-19 in a hospital located in the region of Vale do Itajaí. Methodology: this is a study with a quantitative approach. For data collection, a self-administered questionnaire was used, delivered to nurses and nursing technicians who work on the front lines of COVID-19. Results: Regarding the main difficulties faced by the Nursing team during the pandemic, the following stand out: exhausting work hours, overcoming thoughts that reduce productivity, such as fear, insecurity and contact with patients infected by the virus. As for the challenges faced, the main ones were maintaining security measures, preventing contagion from close people, ensuring emotional balance, and maintaining, even partially, routine activities. Conclusion: The research results showed that the events resulting from the pandemic can generate disease processes, difficulties and challenges for professionals who work in direct care for patients hospitalized with COVID-19. Therefore, it is necessary to promote prevention strategies for the physical and mental illness of these professionals, with a view to minimizing the adverse effects caused by the pandemic.